The contribution of the accuracy of spatial tracking of moving objects to the competitive efficiency of hockey defenders 13-15 years old - Tsepelevich, M.M.; Okuneva, A.S.; Savin, D.N.; Golovanova, I.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to quantify the contribution of the accuracy of spatial tracking of moving objects to the effectiveness of the competitive activity of hockey defensemen aged 13-15. Methods and structure of the study. As part of the sports program of the Sirius Educational Center, 132 hockey defenders, participants in the All-Russian hockey competition "Championship of club teams among boys under 15 years old", were tested. Competitive effectiveness was determined by the indicator of the expected number of team goals, calculated by video analysis of matches. In the course of the study, the task of spatial tracking of moving objects in virtual reality (multiple object tracking task, MOT) and the assessment of special physical fitness (SPT) using the “Complex Test” on ice were performed. The contribution of these factors to competitive efficiency was determined by constructing a multilevel regression model that takes into account the athlete's belonging to the team. Results and conclusions. The accuracy of spatial tracking of moving objects is significantly correlated with the competitive efficiency of hockey defensemen both with and without taking into account the level of SPT. The ability to track the movement of objects during competitive matches does not depend on the special physical qualities of hockey defensemen. This determines the importance of testing the cognitive functions of athletes along with assessing the level of physical fitness. Further research should be aimed at both expanding the testing battery (to assess executive functions, memory, attention, anticipation, etc.) and determining the physiological parameters that characterize the “biological cost” of performing the tests considered in this paper.